Solid-state battery capable of improving acupuncture safety and preparation method
By using porous aluminum foil, low porosity separator and high ionic conductivity solid electrolyte materials in solid-state batteries, combined with the method of reducing the amount of electrolyte, the problem of solid-state batteries getting fire and explosion during needle puncture tests is solved, and the safety of the battery is improved and energy density.
Patent Information
- Application Number
- CN202411704621.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
AI Technical Summary
Existing solid-state batteries are prone to fire and explosion during needle puncture tests, and the use of solid electrolytes increases the contact impedance and electrochemical impedance of the battery cell, deteriorating the electrochemical and safety performance of the battery.
Porous aluminum foil or composite aluminum foil is used as the positive electrode current collector, low porosity and high elongation membranes are used as the substrate, and solid electrolyte materials with high specific surface area and high ionic conductivity are selected for single-side coating of the membrane to reduce the liquid injection of the cell Coefficient to reduce the amount of electrolyte.
By reducing the short-circuit area and current during needle puncture, the accumulation of heat is blocked, the risk of short-circuit thermal runaway is reduced, the intrinsic safety of the battery cell is improved, and the energy density of the battery is improved, so as to achieve the dual improvement of the safety and energy density of the solid-state battery. .
Smart Images

Figure CN119495830A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state battery preparation, and in particular relates to a solid-state battery with improved acupuncture safety and a preparation method thereof. Background Art
[0002] Compared with conventional lithium-ion batteries, solid-state batteries replace conventional ether / carbonate electrolytes with solid electrolytes / gel solid electrolytes and other types of electrolytes. Solid electrolytes replace the use of electrolyte solvents, avoiding thermal runaway caused by low flash point / ignition point of electrolytes. In theory, they can improve the safety of batteries. However, the use of solid electrolytes causes abnormal increase in contact impedance / AC impedance of batteries, which greatly deteriorates the electrochemical performance of batteries. In the actual development process, the more mature methods in the industry still have the presence of electrolytes / solvents, which cannot substantially improve the energy density and safety of batteries. They will also catch fire and explode in the most stringent safety test - the needle puncture test. Therefore, the safety of solid-state batteries deserves further research and consideration, especially the risk of short-circuit thermal runaway caused by needle puncture needs to be effectively resolved.
[0003] At present, the commonly used technical route for solid-state batteries is to use high-energy-density positive and negative electrode materials for the positive and negative electrodes. For example, the positive electrode material is a high-nickel 8 series / 9 series ternary positive electrode material, and the negative electrode uses a silicon-based / graphite composite negative electrode material. The electrolyte uses in-situ polymerization or sulfide solid electrolyte to replace the use of electrolyte, and the diaphragm uses a solid electrolyte diaphragm or a conventional diaphragm. The disadvantages are: 1. The core of needle puncture safety lies not only in the chemical system, but also in the control of short-circuit current and short-circuit area to prevent secondary spread. The addition of solid electrolytes cannot fundamentally solve the problem of needle puncture safety; 2. The electrolyte solvents of gel or in-situ polymerization routes are always present, and flash thermal runaway will also occur in the needle puncture experiment; sulfide solid electrolytes are safe, but they have very strict environmental requirements, and the testing needs to be carried out under high temperature and high pressure. The process route is not conducive to the scale-up and promotion of the product; 3. The use of solid electrolytes increases the contact impedance and electrochemical impedance of the battery cell, which deteriorates the electrochemical performance of the battery, resulting in a double decline in the electrochemical performance and safety performance of the battery. It does not have the theoretical high specific energy and high safety characteristics of solid-state batteries, so innovation and improvement in technical methods are needed.
[0004] Solid-state batteries have high safety characteristics because they use solid electrolytes instead of electrolytes as the medium for lithium ion transmission. However, the ionic conductivity of solid electrolytes at room temperature and pressure is significantly lower than that of liquid electrolyte systems. Using them alone will deteriorate the electrochemical performance of the battery. Therefore, solid-liquid mixed electrolytes or in-situ polymerized gel electrolytes are used during the development process, which will greatly reduce the safety of the battery, and it cannot pass the needle puncture safety test and does not have the intrinsic safety performance of the battery.
[0005] As the most stringent battery safety test, needle puncture simulates the risk of thermal runaway when the battery is subjected to mechanical abuse under actual working conditions. The needle puncture test usually uses a steel needle with a diameter of 1~8mm to puncture the battery at a certain speed or a certain depth, monitor the changes in battery voltage, temperature, pressure and other parameters, and observe whether the battery short-circuits and catches fire or explodes. Through preliminary research, it was found that the key to passing the needle puncture test lies in the area of the short circuit, the current and the speed of heat diffusion at the puncture location. Therefore, the key to improving the safety of solid-state battery needle puncture lies in the study of its mechanism and the control of the short circuit problem after the battery needle puncture, so as to prevent the risk of thermal runaway caused by temperature energy accumulation.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a solid-state battery and a preparation method with improved needle puncture safety, thereby improving the intrinsic safety of the battery cell.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a solid-state battery with improved acupuncture safety comprises the following steps: (1) Using porous aluminum foil or composite aluminum foil as the positive electrode current collector; (2) Using a low-porosity, high-elongation diaphragm as the substrate; (3) Selecting a solid electrolyte material with high specific surface area and high ionic conductivity as a coating for single-sided coating of the diaphragm; (4) Reduce the cell filling coefficient, manufacture the battery according to the conventional route and charge and discharge it normally, and calculate the actual capacity and energy density of the battery.
[0009] Furthermore, in step (1), the elongation at break of the porous aluminum foil is 0.5-1%, the tensile strength is 150-200 MPa, and the number of holes is 200-300 / cm 2 , pore size is 20-50μm.
[0010] Furthermore, in step (1), the composite aluminum foil is obtained by aluminum plating on both sides of PET, wherein the thickness of PET is 8-12 μm, and the thickness of the double-sided aluminum plating layer is 1-3 μm.
[0011] Furthermore, in step (2), the porosity of the diaphragm is 30% to 40%, and the elongation is 40% to 60%.
[0012] Furthermore, the specific surface area of the solid electrolyte material in step (3) is 200-1000 m 2 / g, ionic conductivity is 10 -4to 10 -3 S / cm.
[0013] Furthermore, in step (3), the coating thickness is 3-15 μm.
[0014] Furthermore, in the step (4), the cell filling coefficient is 0.8-1.2 g / Ah, and the amount of free electrolyte after the electrolyte is fully charged is less than 0.1 g / Ah.
[0015] The present invention also provides a solid-state battery prepared by using the method for preparing a solid-state battery with improved needle puncture safety.
[0016] Furthermore, a puncture test was conducted using a steel needle after the battery was fully charged to test the battery voltage, internal resistance and temperature changes. After observation for half an hour, there was no fire or explosion, and the puncture safety test was passed.
[0017] Furthermore, the diameter of the acupuncture needle is 1~5mm, the acupuncture speed is 3~80mm / s, and the acupuncture depth is 3mm~penetration.
[0018] The design mechanism of the present invention is as follows: 1. Use current collector foil with low elongation and low tensile strength, especially aluminum foil. Composite current collectors and perforated current collectors can be used. The purpose is to reduce the area of the puncture peak and the short-circuit area during the puncture process, control the short-circuit time and current, and timely block the accumulation of heat to reduce the risk of short-circuit thermal runaway; 2. Use a low-porosity, high-elongation membrane as the substrate, and select an electrolyte material with a large specific surface area and high ionic conductivity for surface coating to prepare a solid electrolyte membrane. The purpose is to use this electrolyte and membrane to adsorb free electrolyte, reduce the presence of free electrolyte, and reduce the continuous short circuit and heat diffusion caused by electrolyte contact during the acupuncture process. At the same time, the addition of a high-ionic conductivity solid electrolyte and the reduction of electrolyte can improve the ionic conductivity of the battery cell and increase the energy density of the battery; 3. Reduce the injection coefficient of the battery cell and reduce the amount of electrolyte from the source. Similar to the principle of 2, reduce the probability of electrolyte heat spread and thermal runaway caused by needle puncture short circuit; and use it in conjunction with the solid electrolyte in 2 to improve the electrochemical performance of the battery; 4. Assemble the battery with the electrode sheet and the separator normally and conduct a puncture test to observe whether the battery catches fire or explodes and passes the puncture safety test.
[0019] The beneficial effects of the present invention are as follows: a solid-state battery and a preparation method with improved needle puncture safety are invented. The method starts from the needle puncture short-circuit mechanism, reduces the contact area between the foil and the counter electrode, reduces the short-circuit energy and the risk of thermal runaway; adopts a solid electrolyte diaphragm and reduces the amount of electrolyte used to ensure that the battery is short-circuited by needle puncture due to the low flash point / ignition point of the electrolyte. The heat spread and thermal runaway caused by the low flash point / ignition point of the electrolyte are reduced, thereby improving the intrinsic safety of the battery cell, and at the same time improving the energy density of the battery, thereby achieving a double improvement in the safety and energy density of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 The battery of Example 1 passed the puncture test, and the voltage was normal after the puncture.
[0022] Figure 2 The battery in Example 2 did not catch fire or explode after being punctured.
[0023] Figure 3 The battery of Example 3 passed the safety test after being punctured.
[0024] Figure 4 The battery of Example 4 passed the safety test and was disassembled after being punctured.
[0025] Figure 5 Comparative Example 1 caught fire and exploded after being punctured and failed the test.
[0026] Figure 6 Comparative Example 2 caught fire and exploded after being punctured and failed the test.
[0027] Figure 7 Comparative Example 3 caught fire and exploded after being punctured and failed the test.
[0028] Figure 8 Comparative Example 4 caught fire and exploded after being punctured and failed the test.
[0029] Fig. 9 Comparative Example 5 caught fire and exploded after being punctured and failed the test.
[0030] Fig.10 Comparative Example 6 caught fire and exploded after being punctured and failed the test.
[0031] Fig.11 Comparative Example 7 caught fire and exploded after being punctured and failed the test. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0033] The details not described in detail in the present invention are all conventional technical means known to those skilled in the art.
[0034] The method for preparing a solid-state battery with improved acupuncture safety of the present invention comprises the following steps: (1) A porous aluminum foil with a breaking elongation of 0.5-1% and a tensile strength of 150-200 MPa (pore size of 20-50 μm and pore number of 200-300 / cm2) is used. 2 ) or composite aluminum foil (PET thickness is 8~12μm, double-sided aluminum coating thickness is 1~3μm) as the positive electrode current collector; (2) Use a low porosity (30%~40%) and high elongation (40%~60%) diaphragm as the substrate, and select a high specific surface area (200~1000m 2 / g), high ionic conductivity (10 -4 to 10 -3 S / cm) solid electrolyte material is used as a coating on one side of the diaphragm (the coating thickness is 3~15μm); (3) Reduce the cell filling coefficient (0.8~1.2g / Ah) so that the amount of free electrolyte after full charge is less than 0.1g / Ah. Make the battery according to the conventional route and charge and discharge normally, and calculate the actual capacity and energy density of the battery.
[0035] Use a puncture steel needle (diameter 1~5mm) and a puncture speed (3~80mm / s). After the battery is fully charged, conduct a puncture test with a puncture depth of (3mm~penetration). Test the battery voltage, internal resistance and temperature changes. Observe for half an hour to see if there is no fire or explosion and whether it has passed the puncture safety test.
[0036] Example 1 The method for preparing a solid-state battery with improved acupuncture safety in this embodiment comprises the following steps: (1) A porous aluminum foil with a thickness of 12 μm, a breaking elongation of 0.8%, a tensile strength of 166 MPa, and a pore count of 225 / cm 2 , pore size is 25μm, and it is used as the positive electrode current collector of the solid-state battery for electrode coating; the positive electrode formula uses high nickel ternary 9 series material: CNT: PVDF = 97.5:1.25:1.25, and the coating surface density is 28mg / cm 2The negative electrode uses SiOx550:SP:WCNT:CMC:SBR=96:1.5:0.05:1.25:1.1:1.6, and the coating surface density is 9.6mg / cm 2 .
[0037] (2) A low-porosity membrane with a porosity of 33%, an elongation of 58%, and a thickness of 7 μm was used as the substrate; (3) Select a solid electrolyte LLZTO with a specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm is coated as a solid coating on one side of (2) the separator with a thickness of 5 μm, and the positive and negative electrode sheets after coating roller pressing are stacked with the separator to form a battery cell; the number of stacking layers is 15 layers for the positive electrode and 16 layers for the negative electrode, the battery cell size is 80×120 mm, and the battery cell design capacity is 10 Ah.
[0038] (4) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 1.0 g / Ah. After the electrolyte is infiltrated, it is sealed twice and the free electrolyte is measured to be 0.2 g. The battery is manufactured and divided into different capacities according to the conventional route. The charge and discharge current is 0.1C. The actual capacity of the battery is calculated to be 10.8 Ah and the energy density is 352 Wh / kg.
[0039] The needle diameter is 3mm, the needle speed is 20mm / s, and the battery is fully charged to 4.25V for needle test. The test found that the battery passed the needle test. After half an hour of observation, the battery voltage was 4.18V, and the battery did not catch fire or explode, passing the safety test ( Figure 1 ).
[0040] Example 2 The method for preparing a solid-state battery with improved acupuncture safety in this embodiment comprises the following steps: (1) A composite current collector with a thickness of 10 μm, of which the PET thickness is 8 μm, the thickness of the double-sided aluminum coating is 1 μm each, the elongation at break is 1%, and the tensile strength is 192 MPa, is used as the positive electrode current collector of the solid-state battery; (2) A low-porosity membrane with a porosity of 33%, an elongation of 58%, and a thickness of 7 μm was used as the substrate; (3) Select a solid electrolyte LATP with a specific surface area of 600 m 2 / g, ionic conductivity is 5×10 -4 S / cm was applied as a solid coating on one side of the diaphragm with a thickness of 5 μm; (4) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 1.1 g / Ah. After the electrolyte is infiltrated, it is sealed twice and the free electrolyte is measured to be 0.23 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 10.88 Ah and the energy density is 354 Wh / kg.
[0041] The other manufacturing steps of the solid-state battery in this embodiment are the same as those in Embodiment 1.
[0042] The needle diameter is 3mm and the needle speed is 20mm / s. The battery is fully charged to 4.25V for needle test. The test finds out whether the battery has passed the needle test. After half an hour of observation, it is found that the battery has no abnormality, no fire or explosion, and has passed the safety test ( Figure 2 ).
[0043] Example 3 The method for preparing a solid-state battery with improved acupuncture safety in this embodiment comprises the following steps: (1) A porous aluminum foil with a thickness of 12 μm, a breaking elongation of 0.8%, a tensile strength of 166 MPa, and a pore count of 225 / cm 2 , as the positive current collector of solid-state batteries; (2) A low porosity, high elongation membrane with a porosity of 38%, an elongation of 55%, and a thickness of 16 μm was used as the substrate; (3) Select a solid electrolyte LGPS with a specific surface area of 834 m 2 / g, ionic conductivity is 8×10 -4 S / cm was applied as a solid coating on one side of the diaphragm with a thickness of 10 μm; (4) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 1.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times and the free electrolyte is measured to be 0.1 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 9.98 Ah and the energy density is 348 Wh / kg. The other manufacturing steps of the solid-state battery in this embodiment are the same as those in Embodiment 1.
[0044] The needle diameter is 3mm and the needle speed is 20mm / s. The battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. After half an hour of observation, the battery did not catch fire or explode, and passed the safety test ( Figure 3 ).
[0045] Example 4 The method for preparing a solid-state battery with improved acupuncture safety in this embodiment comprises the following steps: (1) A composite current collector with a thickness of 10 μm, of which the PET thickness is 8 μm, the thickness of the double-sided aluminum coating is 1 μm each, the elongation at break is 1%, and the tensile strength is 192 MPa, is used as the positive electrode current collector of the solid-state battery; (2) A low-porosity membrane with a porosity of 33%, an elongation of 58%, and a thickness of 16 μm was used as the substrate; (3) Select a solid electrolyte LLZTO with a specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm was applied as a solid coating on one side of the diaphragm with a thickness of 5 μm; (4) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 1.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times and the free electrolyte is measured to be 0.1 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 10.54 Ah and the energy density is 358 Wh / kg. The other manufacturing steps of the solid-state battery in this embodiment are the same as those in Embodiment 1.
[0046] The needle diameter is 3mm, the needle speed is 3mm / s, the battery is fully charged to 4.25V for needle test, and the test finds out whether the battery has passed the needle test. After half an hour of observation, the battery did not catch fire or explode, and passed the safety test ( Figure 4 ).
[0047] Comparative Example 1 (1) A conventional positive electrode current collector with a thickness of 12 μm, a breaking elongation of 2.5%, and a tensile strength of 259 MPa is used as a positive electrode coating foil for electrode production; (2) A conventional diaphragm with a porosity of 58%, an elongation of 25%, and a thickness of 16 μm was used as the diaphragm substrate of the battery, and an oxide solid electrolyte LLZTO (specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm) surface coating with a coating thickness of 10μm, and then lamination cell production; (3) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 2.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times and the free electrolyte is measured to be 1.65 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 10.64 Ah and the energy density is 328 Wh / kg. The other manufacturing steps of the solid-state battery of this comparative example are the same as those of Example 1.
[0048] The needle diameter is φ3mm, the needle speed is 3mm / s, and the battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. The battery caught fire and exploded about 2s after the needle puncture, and failed the needle puncture safety test ( Figure 5 ).
[0049] Comparative Example 2 (using porous positive electrode current collector) (1) A porous positive electrode current collector with a thickness of 12 μm, a breaking elongation of 0.8%, a tensile strength of 166 MPa, and a pore count of 225 / cm 2 , with a pore size of 25 μm, used as positive electrode coated foil for electrode fabrication; (2) A conventional diaphragm with a porosity of 58%, an elongation of 25%, and a thickness of 16 μm was used as the diaphragm substrate of the battery, and an oxide solid electrolyte LLZTO (specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm) surface coating with a coating thickness of 10μm, and then lamination cell production; (3) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 2.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times and the free electrolyte is measured to be 1.35 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 10.82 Ah and the energy density is 319 Wh / kg. The other manufacturing steps of the solid-state battery of this comparative example are the same as those of Example 1.
[0050] The needle diameter is 5mm and the needle speed is 3mm / s. The battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. About 5s after the needle puncture, the battery swells and catches fire from the side of the aluminum plastic film, and fails the needle puncture safety test ( Figure 6 ).
[0051] Comparative Example 3 (using low porosity and high elongation diaphragm) (1) A conventional positive electrode current collector with a thickness of 12 μm, a breaking elongation of 2.5%, and a tensile strength of 259 MPa is used as a positive electrode coating foil for electrode production; (2) A low porosity, high elongation membrane with a porosity of 33%, an elongation of 58%, and a thickness of 16 μm was used as the substrate, and an LLZTO solid electrolyte with a specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm was applied as a solid coating on one side of the diaphragm with a thickness of 5 μm; (3) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 2.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times and the free electrolyte is measured to be 1.33 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 10.29 Ah and the energy density is 338 Wh / kg. The other manufacturing steps of the solid-state battery of this comparative example are the same as those of Example 1.
[0052] The needle diameter is 3mm, the needle speed is 3mm / s, and the battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. About 2s after the needle puncture, the battery swells and catches fire and explodes, and fails the needle puncture safety test ( Figure 7 ).
[0053] Comparative Example 4 (lowering the injection coefficient) (1) A conventional positive electrode current collector with a thickness of 12 μm, a breaking elongation of 2.5%, and a tensile strength of 259 MPa is used as a positive electrode coating foil for electrode production; (2) A conventional diaphragm with a porosity of 58%, an elongation of 25%, and a thickness of 16 μm was used as the diaphragm substrate of the battery, and an oxide solid electrolyte LLZTO (with a specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm) surface coating with a coating thickness of 10μm, and then lamination cell production; (3) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 1.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times. The free electrolyte is measured to be 0.32 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 9.59 Ah and the energy density is 329 Wh / kg. The other manufacturing steps of the solid-state battery of this comparative example are the same as those of Example 1.
[0054] The needle diameter is 3mm, the needle speed is 3mm / s, and the battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. The battery caught fire and exploded about 3s after the needle puncture, and failed the needle puncture safety test ( Figure 8 ).
[0055] Comparative Example 5 (using porous positive electrode current collector + using low porosity, high elongation separator, normal liquid injection) (1) A porous positive electrode current collector with a thickness of 12 μm, a breaking elongation of 0.8%, a tensile strength of 166 MPa, and a pore count of 225 / cm 2 , with a pore size of 25 μm, used as positive electrode coated foil for electrode fabrication; (2) A low porosity, high elongation membrane with a porosity of 33%, an elongation of 58%, and a thickness of 16 μm was used as the substrate, and an LLZTO solid electrolyte with a specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm was applied as a solid coating on one side of the diaphragm with a thickness of 5 μm; (3) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 2.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times. The free electrolyte is measured to be 0.85 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 10.46 Ah and the energy density is 324 Wh / kg. The other manufacturing steps of the solid-state battery of this comparative example are the same as those of Example 1.
[0056] The needle diameter is 3mm, the needle speed is 3mm / s, and the battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. The battery caught fire and exploded about 2s after the needle puncture, and failed the needle puncture safety test ( Fig. 9 ).
[0057] Comparative Example 6 (Using porous positive electrode current collector + reducing liquid injection) (1) A porous positive electrode current collector with a thickness of 12 μm, a breaking elongation of 0.8%, a tensile strength of 166 MPa, and a pore count of 225 / cm 2 , with a pore size of 25 μm, used as positive electrode coated foil for electrode fabrication; (2) A conventional diaphragm with a porosity of 58%, an elongation of 25%, and a thickness of 16 μm was used as the diaphragm substrate of the battery, and an oxide solid electrolyte LLZTO (with a specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm) surface coating with a coating thickness of 10μm, and then lamination cell production; (3) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 1.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times and the free electrolyte is measured to be 0.11 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 9.88 Ah and the energy density is 335 Wh / kg. The other manufacturing steps of the solid-state battery of this comparative example are the same as those of Example 1.
[0058] The needle diameter is 3mm, the needle speed is 3mm / s, and the battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. The battery caught fire and exploded about 5s after the needle puncture, and failed the needle puncture safety test ( Fig.10 ).
[0059] Comparative Example 7 (Using low porosity, high elongation diaphragm + reducing injection) (1) A conventional positive electrode current collector with a thickness of 12 μm, a breaking elongation of 2.5%, and a tensile strength of 259 MPa is used as a positive electrode coating foil for electrode production; (2) A low porosity, high elongation membrane with a porosity of 33%, an elongation of 58%, and a thickness of 16 μm was used as the substrate, and an LLZTO solid electrolyte with a specific surface area of 518 m 2 / g, ionic conductivity is 5×10 -4 S / cm was applied as a solid coating on one side of the diaphragm with a thickness of 5 μm; (3) After the battery cell is manufactured, the battery cell is injected with liquid at a rate of 1.0 g / Ah. After the electrolyte is infiltrated, it is sealed for two times and the free electrolyte is measured to be 0.26 g. The battery is manufactured according to the conventional route and charged and discharged normally. The actual capacity of the battery is calculated to be 9.86 Ah and the energy density is 330 Wh / kg. The other manufacturing steps of the solid-state battery of this comparative example are the same as those of Example 1.
[0060] The needle diameter is 3mm, the needle speed is 3mm / s, and the battery is fully charged to 4.25V for needle puncture test. The test finds out whether the battery has passed the needle puncture test. The battery caught fire and exploded about 3s after the needle puncture, and failed the needle puncture safety test ( Fig.11 ).
[0061] Through experimental comparison, the solid-state batteries prepared by the conventional method in the comparative examples (Comparative Example 1) or only using a porous positive electrode collector (Comparative Example 2) or only using a low porosity, high elongation separator (Comparative Example 3) or only using a reduced injection coefficient (Comparative Example 4) or using a porous positive electrode collector + using a low porosity, high elongation separator and normal injection (Comparative Example 5) or using a porous positive electrode collector + reducing the injection (Comparative Example 6) or using a low porosity, high elongation separator + reducing the injection (Comparative Example 7) scheme cannot pass the puncture safety test. All the schemes in the embodiments are adopted and improved in application to pass the puncture safety test, which effectively improves the safety of the solid-state battery. In addition, the use of solid electrolytes and the reduction of electrolyte usage can improve the energy density of the battery.
[0062] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a solid-state battery with improved acupuncture safety, characterized in that The following steps are involved: (1) Using porous aluminum foil or composite aluminum foil as the positive electrode current collector; (2) Using a low-porosity, high-elongation diaphragm as the substrate; (3) Selecting a solid electrolyte material with high specific surface area and high ionic conductivity as a coating for single-sided coating of the diaphragm; (4) Reduce the cell filling coefficient, manufacture the battery according to the conventional route and charge and discharge it normally, and calculate the actual capacity and energy density of the battery.
2. The method for preparing a solid-state battery with improved acupuncture safety according to claim 1, characterized in that: In the step (1), the elongation at break of the porous aluminum foil is 0.5-1%, the tensile strength is 150-200 MPa, and the number of holes is 200-300 per cm. 2 , the pore size is 20~50μm.
3. The method for preparing a solid-state battery with improved acupuncture safety according to claim 1, characterized in that: In the step (1), the composite aluminum foil is obtained by aluminum plating on both sides of PET, wherein the thickness of PET is 8-12 μm and the thickness of the double-sided aluminum plating layer is 1-3 μm.
4. The method for preparing a solid-state battery with improved acupuncture safety according to claim 1, characterized in that: In the step (2), the porosity of the diaphragm is 30% to 40%, and the elongation is 40% to 60%.
5. The method for preparing a solid-state battery with improved acupuncture safety according to claim 1, characterized in that: The specific surface area of the solid electrolyte material in step (3) is 200-1000 m 2 / g, ionic conductivity is 10 -4 to 10 -3 S / cm.
6. The method for preparing a solid-state battery with improved acupuncture safety according to claim 1, characterized in that: The coating thickness in step (3) is 3-15 μm.
7. The method for preparing a solid-state battery with improved acupuncture safety according to claim 1, characterized in that: In the step (4), the cell filling coefficient is 0.8-1.2 g / Ah, and the amount of free electrolyte after the electrolyte is fully charged is less than 0.1 g / Ah.
8. A solid-state battery prepared according to the method for preparing a solid-state battery with improved acupuncture safety according to any one of claims 1 to 7.
9. The solid-state battery according to claim 8, characterized in that: Use a steel needle to conduct a puncture test on the battery after it is fully charged to test the battery voltage, internal resistance and temperature changes. After observing for half an hour, if there is no fire or explosion, it passes the puncture safety test.
10. The solid-state battery according to claim 9, characterized in that: The diameter of the acupuncture needle is 1~5mm, the acupuncture speed is 3~80mm / s, and the acupuncture depth is 3mm~penetration.